Jumat Literacy - Ulfah Rahmawati; Fifi Nofiaturrahmah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Information literacy is required to filter all information obtained in order to ensure that the data obtained is truly valid and accountable. Pesantren Misbahul Qur'an, which is proficient in tahfidz and tafsir, pays special attention to students' potential development by providing a schedule of Scientific Literacy activities. It is hoped that the students will be able to improve their ability to recognize when information is required. The Participatory Learning Methods approach is used to deliver this service. The activity has four stages: (1) identification (initial mapping) and material delivery planning, (2) socialization, (3) actualization (material delivery, practice assignment, and presentation), and (4) evaluation and reflection. The results of the service show that students in an Islamic boarding school environment have limited media literacy and have not fully utilized digital in full; the literacy schedule is more towards the search for information that is entertainment in between the busy schedule of activities and targets of memorizing throughm literacy through books and partly utilizing internet media; and the literacy schedule is more towards the search for information that is entertainment in between the busy schedule of activities and targets of memorizing throughm literacy through books and partly utilizing internet media